Response of Nitrogen and Phosphorus Release Flux at the Sediment–Water Interface to the Drainage of Pore Water - Rui LI; Xianqiang TANG; Yanping HU; Shiqiang LU; Junjun GU; Yuanjun SUN (工程科学与技术, 2025)
Pore water plays a key role in sediment nutrient exchange. This study uses electrokinetic geosynthetics (EKGs) as electrodes to drain sediment pore water in the presence of overlying water and conducts five sets of indoor experiments (one control group and four groups exposed to voltage gradients of 0, 0.5 (intermittent power), 0.5 (continuous power), and 1.0 V/cm (intermittent power)) to investigate the performance and mechanisms of pore water drainage in regulating sediment nutrient release and the response of microbial communities. The results showed that draining pore water significantly inhibits the release of nitrogen and phosphorus at the sediment-water interface (SWI). However, the responses of nitrogen and phosphorus exhibit differences. The TN release flux at the SWI shows a gradual downward trend, ranging from –15.698 to 79.903 mg/(m2·d). Within 14 days of the experiment, the TN release flux reduces to within 10% of the maximum release flux. Compared to the control, conducting pore water drainage alone reduces the nitrogen release flux at the SWI by 76.72%. In contrast, the TP release flux at the SWI fluctuates within the 28-day experiment, ranging from –3.558 to 4.279 mg/(m2·d). After the experiment, the pH and LOI of the sediment do not change significantly. TP decreases by approximately 1.06%～5.02% following drainage, while the reduction in TN content occurs primarily near the anode, decreasing by 2.65%～13.63% compared to the initial state. The drainage causes a nonsignificant decline in community abundance indices (the Chao1 index and ACE index of microorganisms in the sediment are slightly reduced) but does not change the dominant species of sediment microorganisms. The dominant phyla are Proteobacteria (13.41%～24.40%), Bacteroides (12.77%～29.71%), and Chloroflexi (5.01%～18.64%). The pH and water content are the primary factors affecting microbial community structure, while the LOI and conductivity of the sediment are secondary factors. The total phosphorus content in the sediment has the least impact. The research demonstrates that the electric drainage of pore water is an economical and low-ecological-impact technology for restricting in-situ sediment nutrient release.